2017
DOI: 10.1111/dom.13123
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and β‐cell function in insulin‐treated patients with type 2 diabetes: A randomized placebo‐controlled 4.3‐year trial

Abstract: In this trial, 390 insulin-treated patients with type 2 diabetes were randomized to either placebo or metformin. Fasting levels of glucose, insulin and C peptide were determined at baseline, after 4 months and yearly thereafter for 4 years to assess fasting estimates of beta cell function. The primary endpoint was the fasting C peptide-to-glucose ratio (FCPGR) and secondary measures were the disposition index (DI) and the fasting C peptide (FCP). We analysed the results with a general linear mixed model. Basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Gastric banding (20)(21)(22) and metformin (23,24) have been shown to improve insulin sensitivity, b-cell function, and glycemia in people with fully developed T2D. In people with IGT or early, mild T2D, we observed no improvement in b-cell function and only modest improvements in glycemia despite large improvements in insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 49%
“…Gastric banding (20)(21)(22) and metformin (23,24) have been shown to improve insulin sensitivity, b-cell function, and glycemia in people with fully developed T2D. In people with IGT or early, mild T2D, we observed no improvement in b-cell function and only modest improvements in glycemia despite large improvements in insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 49%
“…In secondary analyses, we also assessed the alternative hypothesis of a treatment effect from the first visit and remaining constant until the end of the trial [10] by assuming placebo effects at baseline and testing the treatment main effect. Also, we adjusted for eGFR and body mass index as additional covariates in the primary model.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright © Salma Al Kalbani IOD.000622. 5 (5).2022 and the ovary. It also reduces intestinal glucose absorption and hepatic glucose production.…”
Section: Interventions Obes Diabetesmentioning
confidence: 99%
“…One study has shown that metformin can restore the intracellular abnormalities of glucose and FFA metabolism and to restore a normal secretory pattern in rat pancreatic islets especially for those whose secretory function has been impaired by chronic exposure to elevated FFA or glucose levels [3,4]. Another study of 390 insulin-treated patients with type 2 diabetes were randomized to either placebo or metformin found that Fasting C Peptide-to-Glucose Ratio (FCPGR) increased in the metformin group with 1.48 (95% CI, 1.09-1.87, P<0.00) and thus improves long-term estimates of beta cell function in the fasting state [5]. These data might give hope that metformin has potential effect in preserving beta cell function in patients with prediabetic as well as diabetic mellitus.…”
Section: Preserve Beta Cell Functionmentioning
confidence: 99%